Phytochemical composition, antioxidant activity and cytotoxicity of Blumea lacera Linn. from two different habitats (Jahangirnagar University Journal of Biological Sciences, 2016)
Blumea lacera collected from JU campus and the Sundarbans showed strong presence of carbohydrates, flavonoids, trace amount of alkaloids, weak presence of some glucosides, terpenoids and steroids following preliminary phytochemical screening. DPPH free radical scavenging activity increased with the increase of concentration of methanol, ethyl acetate and n-hexane fractions of both the samples. Methanol and ethyl acetate fractions of JU sample showed strong scavenging activity of DPPH free radical. Concentration dependent increment in percent mortality of brine shrimp nauplii was observed in all the fractions of both the samples. Ethyl acetate and methanol fractions of JU sample showed less cytotoxicity than that of Sundarbans samples. Therefore, methanol and ethyl acetate fractions of JU sample should be the choice to identify new bioactive compound(s) in the future.Jahangirnagar University J. Biol. Sci. 3(1): 37-45, 2014 (June)